'We need a physician who is a human being too': exploration of barriers and facilitators for hospitalised palliative patients and their families to discuss advance care planning. (2nd December 2019) - Vanderhaeghen, Birgit; Bossuyt, Inge; De Nys, Katelijne; Menten, Johan; Rober, Peter
Abstract : Background: Advance care planning (ACP) is not well implemented in hospital. Implementation theory stresses the importance of knowing what hospitalised palliative patients and their families experience as barriers or as facilitators in the uptake of ACP with their treating physician. Aims: This study aimed to gain an in-depth understanding of what hospitalised palliative patients and their families experienced as barriers or facilitators for having ACP conversations. Methods: We used a tape-assisted recall procedure to conduct 29 videotaped interviews with hospitalised patients and their families. We used content analysis based on grounded theory principles. Results: Four major fields of tension were discovered: not knowing what to expect from the treating physician; not being sure the treating physician can be a trusted partner; daring to speak about ACP; and staying loyal to one's own wishes. Conclusions: Patients and families need physicians who are accessible and can be trusted ACP partners throughout the disease process.